Aplikasi Penentu Pendonor Darah Potensial di Surabaya Menggunakan Support Vector Machine berbasis Android - Gita Berliany Karaeng; Andreas Handojo; Anita Nathania Purbowo (Jurnal Infra, 2020)
Blood deficiency will be fatal for human body. However, human cannot create nor made blood, so therefore blood donor event is created to gather blood supplies. Blood donor is a voluntary Activity there is no exact amount of blood supplies to be known or predicted. For now, there are little to no media that help people to access the information around blood donor. That is why we need a system to predict potential amount of blood donors in the future and to provide information about blood donor activities.The application will cover two major thing, administrator website application and Android application for donors. Administrator website will be used to organize blood donor activities data. Android application will be used to provide information about blood donor activities to the user. The system can also predict potential donors using Support Vector Machine.The expected product of the program is a system that manage the blood donor activity. Any information about blood donor will be presented to the donors with the Android application. From the experiment and testing, the system can predict the amount of potential and not potential donors in a specific location at a specific time in a certain period.